Does Diversity Drive Down Trust? - Eric M. Uslaner (Fondazione Eni Enrico Mattei (FEEM), 2006)
Some researchers claim that diverse populations lead to less trust. Generalized trust is a core value that leads to positive outcomes in societies
Keywords: Z13; O57; D73; 330; Trust; Diversity; Corruption; from greater tolerance of minority groups and immigrants and willingness to do good deeds; to less corruption; more social welfare and education spending; more open markets; and better functioning government. Generalized trust fundamentally rests upon a foundation of respect for diversity; but at the same time arguing that societies have a common culture. It is the idea that people have a shared fate. Generalized trust rests upon a foundation of economic equality. Yet some claim that diversity leads to less trust rather than more trust. Trusting people who are different from yourself is atypical of most people; they claim. I dispute this; Vertrauen; Ethnische Gruppe; Korruption; Welt; Ethnische Beziehungen